2020
DOI: 10.3390/molecules25081928
|View full text |Cite
|
Sign up to set email alerts
|

Thermocells for Hybrid Photovoltaic/Thermal Systems

Abstract: The photovoltaic conversion efficiency of solar cells is highly temperature dependent and decreases with increasing temperature. Therefore, the thermal management of solar cells is crucial for the efficient utilization of solar energy. We fabricate a hybrid photovoltaic/thermocell (PV/T) module by integrating a thermocell directly into the back of a solar panel and explore the feasibility of the module for its practical implementation. The proposed PV/T hybrid not only performs the cooling of the solar cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Shin et al demonstrated a hybrid photovoltaic thermogalvanic cell module (PV/T) by integrating a TGC directly into the back of a solar panel (Figure 67), exploring the feasibility of the module for practical implementation. 508 Here, a fabricated thermogalvanic cell consisting of an electrolyte with a ferric/ ferrous redox couple ([Fe(CN) 6 ] 4− and [Fe(CN) 6 ] 3− ) and SWCNT electrodes was integrated directly into the back of a commercial solar panel array. The TGC in the fabricated PV/T hybrid system performed both as a cooling system and produced additional power output by converting the thermal energy absorbed by the solar panel into useful electrical energy.…”
Section: Ionic Thermoelectric Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shin et al demonstrated a hybrid photovoltaic thermogalvanic cell module (PV/T) by integrating a TGC directly into the back of a solar panel (Figure 67), exploring the feasibility of the module for practical implementation. 508 Here, a fabricated thermogalvanic cell consisting of an electrolyte with a ferric/ ferrous redox couple ([Fe(CN) 6 ] 4− and [Fe(CN) 6 ] 3− ) and SWCNT electrodes was integrated directly into the back of a commercial solar panel array. The TGC in the fabricated PV/T hybrid system performed both as a cooling system and produced additional power output by converting the thermal energy absorbed by the solar panel into useful electrical energy.…”
Section: Ionic Thermoelectric Materialsmentioning
confidence: 99%
“…Shin et al demonstrated a hybrid photovoltaic thermogalvanic cell module (PV/T) by integrating a TGC directly into the back of a solar panel (Figure ), exploring the feasibility of the module for practical implementation . Here, a fabricated thermogalvanic cell consisting of an electrolyte with a ferric/ferrous redox couple ([Fe­(CN) 6 ] 4– and [Fe­(CN) 6 ] 3– ) and SWCNT electrodes was integrated directly into the back of a commercial solar panel array.…”
Section: State-of-the-art Materialsmentioning
confidence: 99%
See 1 more Smart Citation